Effect of n-type Doping of SnO2 and ZnO on Surface Sites and Gas Sensing Behaviour. (2016) - Marikuts, Artem; Rumyantseva, Marina; Gaskov, Alexander
Abstract: A comparative study of the effect of donor dopants in nanocrystalline ZnO(Ga), ZnO(In) and SnO2 (Sb) obtained by coprecipitation on the microstructure, electronic parameters and surface sites was performed. The observed trends of electron energy surface barrier height and amount of different surface sites depending on doping level (0 – 8 at.%) were correlated with sensitivity to CO, H2 S and NO2 gases. In tin dioxide functionalized by catalytic PdO clusters the doping by Sb resulted in improved conductivity at room temperature. But sensitivity to CO decreased that could be contributed by decreased intergranular energy barriers as well as lower OH-species concentration. Doping of ZnO by Ga or In gave rise to higher dispersion and surface acidity that correlated with the increase of CO sensitivity and decrease of that to H2 S. The sensitivity to NO2 followed non-monotonic trend of donor sites concentration and electron energy surface barrier heights.